Harga Saham Dalam Perspektif Debt to Equity Ratio, Return on Equity dan Earnings Per Share - Ikka Dwi Lestari; Matyani; Ashari Sofyaun (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
The aim of the research is to determine the position of share prices in measuring debt. to Equity Ratio , return on equity and Earning Per Share . The data used are the financial reports of the Food and Beverage sub-sector companies for the period 2020-2023. The findings of the research results show that DER and ROE partially have no effect on stock prices . Other findings show that stock prices can be influenced by the Earning Per Share variable.